2007
DOI: 10.1080/08860220601098839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Higher Dose of Losartan Treatment with Losartan Plus Carvedilol and Losartan Plus Ramipril in Patients with Glomerulonephritis and Proteinuria

Abstract: Background. Proteinuria may cause a worsening of accompanying renal disease or even lead to glomerulosclerosis. There is no data about the effect of carvedilol on patients with proteinuric (>0.5 g/day) glomerulonephritis. This study aimed to compare the effects of carvedilol with ramipril and losartan in patients with proteinuric glomerulonephritis. Methods. Twenty-one glomerulonephritis patients were followed for 12 months. Patients were divided into three groups. All patients were treated with losartan 50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies with Carvedilol showed an attenuated increase in albuminuria, as well as a reduction in cardiovascular events in CKD patients with hypertension [30]. In spite of the finding of favorable effect or the lack of detrimental effect on renal function by the use of betablockers [31], the large randomized clinical HF trials on beta-blocker therapy excluded patients with severe renal dysfunction and did not consider their effects on renal outcome. In the ANZ trial, the creatinine cutoff adopted as exclusion criterion was [2.8 mg/dL, in the CIBIS-II was 3.4 mg/dL, whereas was not specified in the MERIT-HF and in the US Carvedilol Program [32].…”
Section: Beta-blockersmentioning
confidence: 99%
“…Studies with Carvedilol showed an attenuated increase in albuminuria, as well as a reduction in cardiovascular events in CKD patients with hypertension [30]. In spite of the finding of favorable effect or the lack of detrimental effect on renal function by the use of betablockers [31], the large randomized clinical HF trials on beta-blocker therapy excluded patients with severe renal dysfunction and did not consider their effects on renal outcome. In the ANZ trial, the creatinine cutoff adopted as exclusion criterion was [2.8 mg/dL, in the CIBIS-II was 3.4 mg/dL, whereas was not specified in the MERIT-HF and in the US Carvedilol Program [32].…”
Section: Beta-blockersmentioning
confidence: 99%